The Effect of Corporate Governance on Liquidity: Voluntary Disclosure, Analyst Coverage, and Adverse Selection as Mediating Mechanisms - GOH, Beng Wee (Institutional Knowledge at Singapore Management University, 2009)
Our paper examines how a firm’s corporate governance relates to the liquidity (i.e., bidask spread) of its stock. In particular, we focus on how voluntary disclosure, analyst coverage, and adverse selection among investors mediate this relation. Our results show that better corporate governance, in terms of greater board independence and greater institutional monitoring, improves liquidity though more voluntary disclosure, greater analyst coverage, and lower adverse selection. The effects of these mediating mechanisms differ in magnitude. Specifically, we find that the key reason to expect better corporate governance to be associated with improved liquidity is reduced adverse selection. This finding is consistent with the argument that the first order effect of better corporate governance is to constrain agency problems such as insider trading and selective disclosure to some investors, which, in turn, could affect stock liquidity.